THE RISING VIOLENCE AMONG ADOLESCENTS IN KAZAKHSTAN. CONTENT-ANALYSIS OF MEDIA “BOY FROM ABAY VILLAGE” AND “ABUSE IN TURKESTAN” - Summers Danna; Balpeisova Svetlana Asylgireevna; Utemissova Gulmira; Maydangalieva Zhumagul Aldiyarovna (Scientific Journal of Pedagogy and Economics, 2019)
When we speak about bullying, we speak about violence, we as adults are doing our best to make this world, school, and family safe for our kids. The recent study showed that bystanders of bullying in their adult life faced severe mental issues. What is going with the victim of bullying? Each child who suffered from any violence or abuse needs to get medical, public, psychological and legal aid – consequences of violence can become irreversible. The integrated approach and involvement of several professionals is important: social worker, psychologist, and lawyers. The content analysis is the technology of the collection of information made by systematic detection of the characteristics of texts answering the purpose and research problems (concepts, verbs, a phrase and so forth). During our study, we investigated how media and people react in two significant cases. The first case happened in Abay village where in March of seven years old boy claimed he was multiply raped by other kids. This situation caused a colossal resonance in media, social networks.